Work Motivation And Group Mentality As Drivers Of Employee Performance Behavior: Evidence From Manufacturing Companies - Arif Hidayat; Dini Aprianti; Aliy Rasyid (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study analyses the effect of work motivation and herd mentality on employee performance at PT X, a manufacturing company experiencing issues related to absenteeism, declining productivity, and imitative work behaviour during 2022–2024. Methodology: The population consisted of 90 operational staff employees. Using the Slovin formula with a 5% margin of error, a sample size of 74 respondents was determined. A saturated sampling technique was applied, meaning that all employees meeting the research criteria were included as respondents to ensure representativeness. Results: Work motivation and herd mentality have a positive and significant partial and simultaneous effect on employee performance. Findings: Herd mentality is confirmed as an important behavioural factor influencing performance in team-based manufacturing environments. Novelty & Originality: This research extends existing performance literature by incorporating herd mentality as a social–behavioural construct alongside work motivation in a manufacturing context. Empirical evidence from PT X contributes to organisational behaviour research by highlighting the interaction between individual motivational factors and collective behavioural dynamics. Conclusions: Employee performance improvement requires both motivational strategies and effective management of group behavioural patterns. Type of Paper: This paper is a research article.